La industria automotríz: desarrollos en China e implicaciones para Latinoamérica - Kamiya, Marco (2004)
Due to its size and global reach, the automotive industry raises debate when discussing investment attraction policies, strategies for the insertion of productive chains and technology transfer mechanisms. Today this industry combines three important elements: a) it is a leader in productive globalization (e-commerce, subcontracting and commercialization), b) the production of vehicles in China and East Asia is boosting the market and causing changes in strategies and c) the division between original producers and suppliers is consolidating the number of main producers multiplying the number of subcontractors. These new trends, which include productive globalization, China's preponderant role, and new production chains, force private companies to formulate production strategies; and to governments, to offer a successful promotion.